Tide pool treasures - Gish, Melissa (Gish, Melissa. Down in the ocean., 2019)
Investigates the habitat of a tide pool, showcasing the unique animals and plants that make tide pools their homes--including chiton, surf-grass, and starfish. Includes information on how governments around the world are protecting tide pool habitats, as well as a glossary.